Analisis Kinerja Motor Terhadap Kerusakan Kompresor Tipe B – 304 pada LRT Jakarta Seri 1100 - Wahyu Hari Nugroho; I Gede Eka Lesmana; Rovida Camalia Hartantrie (Fakultas Teknik Universitas Pancasila, 2022)
Compressor is one of the energy conversion machines that has a function to compress or compress the working fluid, in this case compressible fluid. To maintain the reliability of components carried out maintenance including periodic maintenance and maintenance when there is damage, in this final task obtained data on the 71st weekly maintenance obtained compressor is not able to supply air optimally. Output power obtained output power of 61,475 kW, while in data processing obtained the largest output power obtained by 85.6 kW large output power based on high current input due to excess load on the motor. The amount of output power that exceeds the maximum output power results in a fracture in the piston rod. And get a filter that has been dirty on the compressor so that the air can not be compressed to the maximum.